2021
DOI: 10.1177/15347346211004141
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antimicrobial Resistance and the Compatibility of Initial Antibiotic Treatment on Clinical Outcomes in Patients With Diabetic Foot Infection

Abstract: We aimed to determine pathogen microorganisms, their antimicrobial resistance patterns, and the effect of initial treatment on clinical outcomes in patients with diabetic foot infection (DFI). Patients with DFI from 5 centers were included in this multicenter observational prospective study between June 2018 and June 2019. Multivariate analysis was performed for the predictors of reinfection/death and major amputation. A total of 284 patients were recorded. Of whom, 193 (68%) were male and the median age was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
0
18
0
8
Order By: Relevance
“…144 But, as these antibiotics are often used in more severe or nonresponsive cases, it is difficult to draw clear conclusions. 144 Given the paucity of data on the resolution of infection, recurrence of infection, and the acquisition of antimicrobial resistance, our recommendation is to choose any of the systemic antibiotic regimens that have shown to be effective in published randomised controlled trials to treat a patient with diabetes and a soft tissue infection of the foot. Antibiotic dosing for skin and soft tissue infection is usually standard, but therapy for DFO may require higher doses than standard doses.…”
Section: Rationalementioning
confidence: 99%
“…144 But, as these antibiotics are often used in more severe or nonresponsive cases, it is difficult to draw clear conclusions. 144 Given the paucity of data on the resolution of infection, recurrence of infection, and the acquisition of antimicrobial resistance, our recommendation is to choose any of the systemic antibiotic regimens that have shown to be effective in published randomised controlled trials to treat a patient with diabetes and a soft tissue infection of the foot. Antibiotic dosing for skin and soft tissue infection is usually standard, but therapy for DFO may require higher doses than standard doses.…”
Section: Rationalementioning
confidence: 99%
“…43,44 Following our 2019 review, we identified 3 additional, recent papers that compared the efficacy of different systemic antibiotics for the treatment of ST-DFIs. 14,21,33 In a series of 794 initial episodes of DFIs in 419 patients, including 339 episodes of DFO, all patients were treated with surgical debridement. 14 Beta-lactam antibiotics were used in 631 episodes (79%) including oral amoxicillinclavulanate at a daily dose ranging from 2 to 3 g for a median of 20 days (interquartile range, 12-30 days) in 301 episodes.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…This limitation makes it difficult to draw reliable conclusions. 33 We added 'acquisition of antimicrobial resistance' in the 2023 PICO, a term that was not included in the 2019 PICO. We did not find outcome data for antimicrobial resistance in the extracted data of the papers identified in the 2019 systematic review.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Although there is insufficient evidence that MDRO delay wound healing, 15 some studies have shown that MDRO significantly increase the rate of recurrence and amputation in patients with DFU. 16 , 17 There are significant differences in the prevalence of MDROs in different regions, 18–21 and there are few reports on the prevalence of MDROs in DFU in North China. The aim of this study is to analyze the microbiological characteristics of DFU and drug resistance of MDROs, and to reveal the potential risk factors for MDROs.…”
Section: Introductionmentioning
confidence: 99%